2010
DOI: 10.1258/mi.2010.010028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovariectomy and Estrogen Replacement Therapy on Visceral Adipose Tissue and Serum Adiponectin Levels in Rats

Abstract: We conclude that ovarian hormone withdrawal leads to higher body weight and visceral adipose tissue in rats, but surprisingly does not change adiponectin levels. Although a substantial decrease in body weight was achieved by estrogen replacement therapy in OVX animals, the beneficial metabolic effects of weight loss seems to be only mechanical, having a tendency to improve insulin sensitivity without elevating adiponectin production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
38
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 34 publications
12
38
2
4
Order By: Relevance
“…Our previous studies (Pipatpiboon et al, 2012;Pratchayasakul et al, 2011b) and the present study confirmed that obesity induced by HF consumption impaired peripheral insulin sensitivity, as indicated by increased body weight, visceral fat, plasma glucose level, plasma insulin level, HOMA index, and the total area under the curve (TAUCg). In addition, it has been shown that estrogen deprivation alone also caused obesity, leading to the development of peripheral insulin resistance (Alonso et al, 2006;Babaei et al, 2010). Consistent with those studies, this study showed that 8 weeks after a bilateral ovariectomy, rats had both increased body weight and visceral fat, leading to reduced peripheral insulin sensitivity.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous studies (Pipatpiboon et al, 2012;Pratchayasakul et al, 2011b) and the present study confirmed that obesity induced by HF consumption impaired peripheral insulin sensitivity, as indicated by increased body weight, visceral fat, plasma glucose level, plasma insulin level, HOMA index, and the total area under the curve (TAUCg). In addition, it has been shown that estrogen deprivation alone also caused obesity, leading to the development of peripheral insulin resistance (Alonso et al, 2006;Babaei et al, 2010). Consistent with those studies, this study showed that 8 weeks after a bilateral ovariectomy, rats had both increased body weight and visceral fat, leading to reduced peripheral insulin sensitivity.…”
Section: Discussionsupporting
confidence: 89%
“…In the study, ovariectomy resulted in a significant increase in body weight and also an increase in visceral fat, confirming previous findings [36,37], This indicates that the lack of estrogen following ovariectomy influences body weight, partially by increasing visceral fat [1,3]. Estrogen plays a crucial role in distributing visceral fat, probably by changing lipoprotein lipase activity [1,3,38].…”
Section: Discussionsupporting
confidence: 88%
“…In OVX animals it was possible for there to be a substantial reduction in body weight via estrogen replacement therapy, due to improved insulin sensitivity, but without an increase in adiponectin production meaning that the beneficial metabolic effects of the weight loss were from a mechanical perspective. 29 One of the challenges associated with the menopause is weight gain due to increased visceral fat, which was linked to as diabetes, hypertension and dyslipidemia. 30 There is mild obesity in the ovariectomized animal model so it can help indicate how adiposity is altered by hypoestrogenism.…”
Section: Discussionmentioning
confidence: 99%